Identifying and assessing the environmental aspects related to Yazd solar thermal power plant effluent - saman mousavi; Ahad Sotoudeh; Hamidreza Azimzade; Bahman Kiani (Mashhad University of Medical Sciences, 2017)
Background and Objectives: Environmental management system attempts to create and pursue requirements for the organizations to prevent catastrophic damages causing to their surroundings. One of the most important environmental aspects of thermal power plants is the impact on water resources. Moreover to high level consumption, the produced wastewaters will added to other pollutants. Methods: The produced wastewater from the combined cycle power plant was monitored during one year. To compare pollutants from industrial wastewater with environmental standards, Kolmogorov-Smirnov's test was employed. The main aspects of wasting and contaminating consumed water resources of power plant has been studied by using Preliminary Hazard Analysis and William fine techniques. Also the effective actions were performed to decrease and monitor the determined aspects. Results: The results have been showed that industrial wastewater has not any heavy elements contamination with 99 percent of certainty. Among the effective risks on water resources, 77 risks with low priority, 60 risks with medium priority and 12 risks with high priority has been identified. The chemistry refinery's section and steam's unit had the most identified risks. Among the risk controlling strategies, reducing risk's intensity with 73 percent is the most effective strategy. Also, 14 percent of strategies refer to exclusion, 10 percent to transfer and three percent to acceptance of risk Conclusion: Combining risk assessment methods and environmental pollutants concentration measurements could increased the accuracy and validity of the results by systemizing the identification process.